2016
DOI: 10.5457/p2005-114.152
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health-promoting lifestyle of first and second year medical students

Abstract: Objective -The aim of the study was to examine the relationship between physical activity intensity levels and health-promoting lifestyle among Croatian first and second year medical students. Materials and methods -The cross sectional study was conducted on a sample of first and second year students (n=885). Data were collected by means of a self-administered anonymous questionnaire: The International Physical Activity Questionnaire (IPAQ -long form) and The HealthPromoting Lifestyle Profile [HPLP II] (Adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…While some research indicates that various periods of study such as examinations and placement practice can lead to higher experiences of stress (Sun & Zoriah, 2015 ), Bewick et al (2010) have suggested that stress commences in the initial semester for students and does not abate throughout the time in university. There are numerous factors that may explain this, predominantly related to the onset of academic demands, the need to adapt to new circumstances and the significant life and identity changes student make as they transit from adolescence into adulthood (Opoku-Acheampong et al, 2017 ; Bhandari, 2012 ; Cage et al, 2021 ; Charalambous, 2020 ; Chen et al, 2013 ; Mašina et al, 2016 ). Furthermore, the introduction of higher fees and the more competitive employment market have been identified as creating the context for higher levels of stress for students in the UK and Ireland (Money et al, 2017 ; O.Leary, 2019 ).…”
Section: First Year Students and Transition To Universitymentioning
confidence: 99%
“…While some research indicates that various periods of study such as examinations and placement practice can lead to higher experiences of stress (Sun & Zoriah, 2015 ), Bewick et al (2010) have suggested that stress commences in the initial semester for students and does not abate throughout the time in university. There are numerous factors that may explain this, predominantly related to the onset of academic demands, the need to adapt to new circumstances and the significant life and identity changes student make as they transit from adolescence into adulthood (Opoku-Acheampong et al, 2017 ; Bhandari, 2012 ; Cage et al, 2021 ; Charalambous, 2020 ; Chen et al, 2013 ; Mašina et al, 2016 ). Furthermore, the introduction of higher fees and the more competitive employment market have been identified as creating the context for higher levels of stress for students in the UK and Ireland (Money et al, 2017 ; O.Leary, 2019 ).…”
Section: First Year Students and Transition To Universitymentioning
confidence: 99%
“…A number of studies have assessed health-promoting behaviors in student populations around the world [ 19 , 20 , 21 , 22 , 23 , 24 ] using the Health-Promoting Lifestyle Profile II (HPLP II), first described by Walker et al [ 18 ]. In Croatia, health-promoting lifestyles have previously been assessed among medical students [ 25 , 26 ]. However, such data for the population of dental students is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Health-promoting lifestyle behaviors among adolescents are drawing great attention worldwide (Almutairi et al, 2018). There are many studies in the literature assessing the health-promoting behaviors of university students in the United States (USA), Europe and Asian countries (Kara & İşcan, 2015;Borle et al, 2008;Mašina et al, 2016;Yahia et al, 2016). However, no study has been conducted on lifestyle behaviors that improve health among university students in Somalia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies conducted with university students have shown that the HPLP-II exercise sub dimension has the lowest mean score (Kara & İşcan, 2016;Alzahrani et al, 2019;Shaheen et al, 2015). However, Mašina et al (2016), who found moderate scores in the exercise sub dimension, stated that the average score obtained by the students for the health responsibility sub dimension was the lowest.…”
Section: Discussionmentioning
confidence: 99%